Implementasi Analisis NIDS Berbasis Snort Dengan Metode Fuzy Untuk Mengatasi Serangan LoRaWAN - Della Vinka Sandi; Muhammad Arrofiq (Ikatan Ahli Informatika Indonesia (IAII), 2018)
Indonesia is one of agrarian countris which has a fertile soil condition, but the agricultural products nowadays are not maximal in certain areas particularly strawberry plantation. Strawberry plant it self needs precise temperature and humidity level to maximize strawberry harvest. Soil humidity and air temperature are changing many times caused by the weather. Therefore, this research will build a prototype which is called Smart Agriculture for monitoring the temperature and soil humidity in strawberry plantation. Temperature and soil humidity data will be sent through wireless transmission media to smartphone using LoRa and LoRaWAN technology. This technology could send the data in a long distance but it's server is vulnerable to attacks such as flooding payload data from LoRa node, ping of death or ping flooding, and scanning port. This research implements that attack on LoRaWAN network server which influences server bandwidth , delay, jitter, and throughput from normal condition. To detect an attack, Snort NIDS method and attack classification are used with fuzzy logic method. The result of this research are temperature and humidity readings, attack notification, and attacker address blocking. Besides, it has proven that fuzzy and snort can optimize server performance.